2022
DOI: 10.1101/2022.11.11.516108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuromodulatory organization in the developing rat somatosensory cortex

Abstract: The vast majority of cortical synapses are found in the neuropil which is implicated in multiple and diverse functions underlying brain computation. Unraveling the organizing principles of the cortical neuropil requires an intricate characterization of synaptic connections established by excitatory and inhibitory axon terminals, of intrinsic and extrinsic origin and from ascending projections that govern the function of cortical microcircuits through the release of neuromodulators either through point-to-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…ACh neurons and nAChRs can be detected from an early time point in the embryonic brain but the findings vary based on the experimental conditions ( Cimino, 1995 ; Jaarsma et al, 1997 ; Zhang, 1998 ; Abreu-Villaca et al, 2011 ; Zhang et al, 2016 ; Broide et al, 2019 ; Abbasi et al, 2020 ; Alzu’bi et al, 2020 ; Colangelo et al, 2022 ; Saad et al, 2022 ). While it has been shown that hindbrain CN neurons are born approximately at E9, basal forebrain ACh neuron between E10 and E13.5, and neurons in the habenula between E14 and E18, the date of birth does not explain when ACh neurons become cholinergic ( Finlay and Darlington, 1995 ; Allaway et al, 2020 ; Ananth et al, 2023 ; Funato et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACh neurons and nAChRs can be detected from an early time point in the embryonic brain but the findings vary based on the experimental conditions ( Cimino, 1995 ; Jaarsma et al, 1997 ; Zhang, 1998 ; Abreu-Villaca et al, 2011 ; Zhang et al, 2016 ; Broide et al, 2019 ; Abbasi et al, 2020 ; Alzu’bi et al, 2020 ; Colangelo et al, 2022 ; Saad et al, 2022 ). While it has been shown that hindbrain CN neurons are born approximately at E9, basal forebrain ACh neuron between E10 and E13.5, and neurons in the habenula between E14 and E18, the date of birth does not explain when ACh neurons become cholinergic ( Finlay and Darlington, 1995 ; Allaway et al, 2020 ; Ananth et al, 2023 ; Funato et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is essential to study the location and composition of cholinergic synapses, nicotinic, as well as muscarinic receptors at different developmental time points similar to recent research at the neuromuscular junction ( York and Zheng, 2017 ; Badawi and Nishimune, 2018 ). Besides, the development of the cholinergic system should be assessed in relationship with other neurotransmitter or neuromodulator systems on a whole-brain level ( Colangelo et al, 2022 ). Lastly, ACh neurons coexpress GABAergic markers during development, and GABA cotransmission is important for mature brain function ( von Bartheld and Rubel, 1989 ; Goral et al, 2022 ; Granger et al, 2023 ; Lozovaya et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation